MENINGKATKAN KEMAMPUAN MINAT BERHITUNG MELALUI PERMAINAN SONDAH MODIFIKASI - Dewi Arini; Agus Sumitra (IKIP Siliwangi, 2019)
This study purpose of was to determine the effectiveness of modification play methods in improving numeracy skills in early childhood. The research method used is a quasi-experimental method using a non-equivalent control group design that is using two classes. Data collection techniques in this study used observation, interviews and documentation studies. The data analysis is done by using descriptive data for qualitative data, and using statistics for quantitative data. Based on the normality and homogeneity test, pretest and posttest data are normally distributed and the variance is homogeneous because all the significance is greater than 0.05. The data of this study have a 0.02 2-tailed significance value which means less than 0.05, so the data has a significant difference in the ability to recognize the concept of numbers between experimental classes given the modification method and the control class given the conventional method. The normalized gain test calculation shows that the N-Gain Score for the experimental class of 78.3% belongs to the very effective category. While the N-Gain Score of the control class was 52.9%, included in the less effective category.Tujuan penelitian ini untuk mengetahui efektifitas metode bermain sondah modifikasi dalam meningkatkan kemampuan berhitung pada anak usia dini. Penelitian ini menggunakan metode metode quasi eksperimen dengan menggunakan desain kelompok kontrol non ekuivalen yaitu menggunakan dua kelas. Data pada penelitian ini dikumpulkan dengan teknik observasi, wawancara dan studi dokumentasi. Berdasarkan uji normalitas dan homogenitas, kedua data menunjukkan kenormalan dan variansnya homogen karena semua signifikasinya lebih besar dari 0,05. Data penelitian ini memiliki nilai signifikasi 2-tailed 0,02 yang artinya kurang dari 0.05, maka data tersebut memiliki perbedaan yang cukup signifikan pada kemampuan minat berrhitung antara kelas eksperimen yang diberi metode sondah modifikasi dan kelas kontrol yang diberi metode konvensional. Perhitungan uji gain ternormalisasi menunjukkan bahwa N-Gain Score untuk kelas eksperimen sebesar 78,3% termasuk ke dalam kategori sangat efektif. Sementara N-Gain Score kelas control sebesar 52,9% termasuk ke dalam kategori kurang efektif.